Meta‑analysis of ileal digestibility of amino acids and minerals in pigs fed diets containing enzymes - Lehnen, Cheila Roberta; Lovatto, Paulo Alberto; Andretta, Ines; Kipper, Marcos; Huaschild, Luciano; Rossi, Carlos Augusto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate the effect of phytase and xylanase on the apparent ileal digestibility (aID) of amino acids, calcium and phosphorus in growing pigs through meta-analysis. The database consisted of 21 articles published between 1998 and 2009, with a total of 82 treatments and 644 pigs. A meta-analysis was performed by graphical, correlation, variance and covariance analyses. Concentrations of phytic phosphorus and the fractions neutral detergent fiber, acid detergent fiber and acid detergent lignin, in the diet, showed a low and negative correlation with aID of calcium, phosphorus and amino acids. The addition of phytase in the diets increased the aID of arginine in 2%, calcium in 14% and phosphorus in 34%. The aID of arginine, phenylalanine, isoleucine and lysine was 3.3% higher in pigs fed diets containing xylanase, in comparison to the diets without the enzyme. Phytic phosphorus and fiber in the diets reduce the aID of calcium, phosphorus and essential amino acids. The use of phytase and xylanase in the diets improves the utilization of calcium, phosphorus and some amino acids. However, excessive calcium and phosphorus in the diets reduces the phytase action on the ileal digestibility of the nutrients.